ERAS—Anticipated outcomes and realistic goals. Issue 5 (5th September 2017) - Manso, Maria; Schmelz, Jacob; Aloia, Thomas
Abstract : Enhanced recovery programs emphasize implementation of perioperative measures to reduce stress and restore baseline function. Complications and length of stay are greatly improved as a result, but the field is moving toward more patient centric and longer term outcomes that better reflect functional recovery. Programs demonstrating value in these domains will undoubtedly see corollary gains in traditional metrics. Thus, greater focus on patient well‐being and treatment success is key to successful implementation of enhanced recovery. Abstract : The optimal approach when initiating an enhanced recovery program is to focus on patient‐centric well‐being and outcomes. Programs that demonstrate value in these domains will see corollary gains in more physician/hospital centric metrics. Basically, the residue of a well‐intentioned enhanced recovery program is shorter LOS, decreased complication rates and lower costs of care.